Effectiveness of Health Education Using Booklets Towards Ability Self-Care for Heart Failure Patients - Imam Mashudy Fazry; Beti Kristinawati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Heart failure remains a major global health problem, contributing to high morbidity and mortality, particularly among older adults. Effective self-care is essential to maintain clinical stability and improve the quality of life in patients with chronic heart failure. This study aims to increase the effectiveness of family-based health education by using a booklet containing self-care skills for heart failure patients. A quasi-experimental one-group pretest-posttest design was conducted at a regional hospital in Surakarta, involving 148 patients selected through purposive sampling. Data were collected using the Self Care of Heart Failure Index (SCHFI) version 6.2 and analyzed with the Wilcoxon Signed Rank Test. Results showed a significant improvement in self-care scores from pretest (mean = 53.60) to posttest (mean = 63.18), with an average increase of 9.58 points (17.87%; p < 0.001). The findings indicate that family-centered education through a booklet significantly enhances patients' self-care, maintenance, and management, and increases their confidence. This intervention strengthens family involvement, increases health knowledge and self-efficacy, and supports sustainable home-based care. The study contributes to nursing science by providing empirical evidence that simple, low-cost educational media can effectively empower families and improve self-care outcomes in chronic heart failure management, underscoring the importance of family engagement in patient-centered care.